(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the role of metaphors and metonymy in the formation of euphemisms in the Spanish language. Euphemisms, as linguistic tools used to soften or indirectly address sensitive, taboo, or unpleasant subjects, are often constructed through the cognitive mechanisms of metaphor and metonymy. These figures of speech allow for the transformation of potentially harsh or stigmatized concepts into more acceptable or socially appropriate expressions. By examining examples from contemporary Spanish, this study illustrates how metaphors and metonymy facilitate the creation of euphemisms that align with societal norms and values. The research highlights the cognitive processes involved in the construction of euphemisms, emphasizing their significance in communication, social interaction, and cultural adaptation. Furthermore, the article provides a comparative analysis of euphemisms derived from metaphorical and metonymical shifts, offering insights into how language shapes the perception of delicate topics.